Reader’s theatre to improve students’ comprehension - Siti Ainun Jariyah, Hassan; Hamizah, Zahari; Azlina, Mohd Ariffin (2018)
The purpose of this study is to find out whether using Reader’s Theatre had a significant influent to improve students’ comprehension in reading. In Malaysia, English language is used and taught as a second language. However, for some of the foreign students that come to Malaysia to study, there are having difficulties to use English and English may be a third language for them. It is important to use a method that is engaging enough to encourage the students to read aloud and the most important is to help them understand the text that they read. The samples for this study are 10 foreign students. The data were collected by distributing literature response questions form to test students’ reading comprehension. All of the students were given the form before and after Reader’s Theatre. Hence, using Reader’s Theatre has a positive impact on improving students’ reading comprehension and it also provides opportunities for the students to improve their pronunciation and to be more confident. Reader’s Theatre is also proven to improve students’ reading interest and motivation.